Impaired neutrophil and monocyte chemotaxis in chronic and aggressive periodontitis and effects of periodontal therapy - R Santhosh Kumar; Shobha Prakash (Wolters Kluwer Medknow Publications, 2012)
Background and Objectives: Depressed chemotactic activity of polymorphoneutrophil (PMN) and monocyte (MN) appears to be one of the significant risk factors in the development of periodontal disease. Although bacteria are the primary etiologic factor in periodontal disease, the patient's host response is a determinant of disease susceptibility. Depressed chemotaxis of PMN and MN could lead to periodontal destruction by altering the host response i.e. impairment of the normal host response in neutralizing infection and alterations that result in destruction of the surrounding periodontal tissues. Materials and Methods: Thirty patients (10 healthy subjects, 10 chronic periodontitis, and 10 with aggressive periodontitis) participated in this study. Clinical parameters like plaque index, gingival index, probing pocket depth, and radiographic assessment were done. The peripheral blood PMNs and MNs were isolated from the patient and the chemotactic response was studied. Statistical analysis was performed using post-hoc Newman-Keul range test. Results: PMN and MN chemotaxis was found to be statistically significant (P<0.05) at baseline and three months after periodontal therapy in chronic and aggressive periodontitis group compared to healthy subjects. However on comparison between chronic and aggressive periodontitis group statistical significance was not found (P>0.05).Comparision between chronic periodontitis, aggressive periodontitis with healthy subjects, PMN and MN chemotaxis showed statistical significance (P<0.05) at baseline and three months after periodontal therapy, Whereas statistically there was no difference when chronic periodontitis was compared with aggressive periodontitis Interpretation and Conclusion: Depressed chemotaxis of PMN and MN results in increased periodontal destruction. In this study, depressed PMN and MN chemotaxis is seen in both aggressive periodontitis group and chronic periodontitis group and the response was altered although to a lesser degree after periodontal therapy in both groups indicating that effect of treatment does exist.